Peran Orangtua PERAN ORANGTUA DALAM MENANAMKAN SIKAP ASERTIF TERHADAP ANAK USIA DINI DI MASA PANDEMI COVID-19 - Mega Cahya Dwi Lestari (Generasi Emas: Jurnal Pendidikan Islam Anak Usia Dini, 2021)
The role of parents for their children is as a guide in growth and development and also character planting. Parents are first and foremost responsible for the education of their children. Assertiveness is an ability to communicate what is desired, confidently, decisively, honestly, while maintaining the feelings of others. Assertiveness can be instilled from an early age because by having an assertive attitude a child will get used to and easily socialize with an effective age environment. Furthermore, children will be able to express what they feel and want directly, honest children will avoid the emergence of uncomfortable feelings due to holding and keeping something they want to say. The role of parents in instilling an assertive attitude during this Covid-19 pandemic in children must be very high and it is highly expected that parents can provide a good foothold and stimulus for their children so that children have a good attitude. Children who are instilled assertiveness by their parents can easily find solutions and solutions to various problems they face. Parents are the right place to instill an assertive attitude in children from as early as possible, because assertiveness is not something outward but rather a pattern of attitudes and behavior that is learned repeatedly. And if the child chooses to be assertive, the parents are more direct with words and polite ways